Mekanisme Penetapan Berakhirnya Pemeriksaan dan Pembukaan Kembali Sidang Arbitrase dalam Perspektif Hukum Acara Arbitrase di Indonesia - Andromeda Bintang Wardhana; Mori ramadhan; Naufal aura Bagaskara (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This article examines two essential mechanisms in the arbitration process: the determination of the closure of proceedings and the reopening of hearings. The closure of proceedings is a formal stage that signifies the completion of the evidentiary process and serves as the basis for the arbitral tribunal to begin deliberations and draft the final award. Meanwhile, the reopening of hearings is an extraordinary mechanism that may only be invoked under limited circumstances, such as the discovery of new evidence (novum), fraud, or significant procedural errors. This study employs a normative juridical method through an analysis of Law No. 30 of 1999, BANI Rules, and international arbitration instruments such as the ICC Rules. The findings indicate that these mechanisms must be carried out carefully in order to maintain a proper balance between efficiency, legal certainty, and substantive justice. The article underscores the importance of official documentation, procedural limitations, and the authority of arbitrators in managing both the closure of proceedings and reopening, ensuring that arbitration remains an effective dispute resolution forum.